Do circulating neutrophil extracellular traps predict recurrence in early breast cancer? - Martinez-Cannon, Bertha Alejandra; Garcia-Ronquillo, Karen; Rivera-Franco, Monica M.; Leon-Rodriguez, Eucario (Frontiers in Oncology, 2023)
Background Neutrophil extracellular traps (NETs), three-dimensional structures formed by neutrophil enzymes such as neutrophil elastase (NE) and nuclear components (DNA), have been associated with progression and metastasis in breast cancer (BC). Thus, the aim of this study was to evaluate the association of circulating NETs with clinicopathological characteristics and outcomes in early BC. Methods A prospective cohort included women with newly diagnosed early BC. NETs were defined as the presence of NE-DNA complexes in plasma, measured by optical density. Levels of NETs were dichotomized according to the median, as low and high levels of circulating NETs. Fisher’s exact test was used to evaluate associations between NETs and clinicopathological characteristics and outcomes. Survival was assessed using the Kaplan Meier method and log-rank test. Results Forty patients were included, 23 (57.5%) patients with low and 17 (42.5%) with high levels of circulating NETs. No associations were found between clinicopathological characteristics and circulating NETs levels. Recurrence (p = 0.99) and site of recurrence (p = 0.99) were not statistically associated with plasma NETs levels. Overall, recurrence-free survival was not statistically different between circulating levels of NETs. Conclusions With a short follow-up and low number of events, our results suggest that circulating levels of NETs at diagnosis of early BC are not associated with more aggressive clinicopathological characteristics, recurrence, or site of recurrence.